2014
DOI: 10.1148/radiol.13121999
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Monitoring of Radiofrequency Ablation and Postablation Assessment: Accuracy of Contrast-enhanced US in Experimental Rat Liver Model

Abstract: Purpose:To examine the accuracy of the unenhanced zone at contrast material-enhanced ultrasonography (US) in predicting coagulative necrosis during and 21 days after radiofrequency (RF) ablation by using radiologic-pathologic comparison. Materials and methods:Animal studies were approved by the Institutional Animal Care and Use Committee. The livers of 28 rats underwent US-guided RF ablation. In four animals, contrast-enhanced US was performed during ablation and 2 hours and 2, 7, 14, and 21 days after ablatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…This result is consistent with a previous study in which a damaged zone eventually transitioned to non-viability within 2 days after RF ablation. 12 The study reported that lightly stained peripheral zone on NADH staining increased rapidly within 2 h after ablation. 12 However, we did not notice a rapid increase in the lightly NADH-stained peripheral zone up to 2 h after RF ablation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This result is consistent with a previous study in which a damaged zone eventually transitioned to non-viability within 2 days after RF ablation. 12 The study reported that lightly stained peripheral zone on NADH staining increased rapidly within 2 h after ablation. 12 However, we did not notice a rapid increase in the lightly NADH-stained peripheral zone up to 2 h after RF ablation.…”
Section: Discussionmentioning
confidence: 96%
“…12 The study reported that lightly stained peripheral zone on NADH staining increased rapidly within 2 h after ablation. 12 However, we did not notice a rapid increase in the lightly NADH-stained peripheral zone up to 2 h after RF ablation. The reason for this discrepancy is not clear and further study on this issue is needed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Contrast-enhanced imaging studies such as contrast-enhanced MRI (CEMRI), contrastenhanced CT (CECT) and contrast-enhanced ultrasound (CEUS) have been widely used to evaluate the treatment response. [4][5][6][7][8] The disappearance of arterial enhancement in the treated tumour region and an adequate safety margin on contrast-enhanced imaging studies indicate a successful treatment. 5,6 However, in general, the patients have to wait 1 month or more until the peritumoral hyperaemia reaction around the ablation zone disappears when these contrastenhanced imaging studies are applied, and the immediate contrast-enhanced imaging studies after RFA have been regarded as insufficient.…”
Section: Introductionmentioning
confidence: 99%